Cold-Spray Coatings Recent Trends and Future perspectives (Springer International Publishing, 2018)
This book combines the contributions of experts in the field to describe the behavior of various materials, micromechanisms involved during processing, and the optimization of cold-spray technology. It spans production, characterization, and applications including wear resistance, fatigue, life improvement, thermal barriers, crack repair, and biological applications. Cold spray is an innovative coating technology based on the kinetic energy gained by particles sprayed at very high pressures. While the technique was developed in the 1990s, industrial and scientific interest in this technology has grown vastly in the last ten years. Recently, many interesting applications have been associated with cold-sprayed coatings, including wear resistance, fatigue life improvement, thermal barriers, biological applications, and crack repair. However, many fundamental aspects require clarification and description.